ADDITIONS TO THE FERN FLORA OF JAVA - RE Holttum (REINWARDTIA, 1974)
Cyathea jacobsii (Cyatheaceae), Pneumatopteris auctipinna and Pseu-dophegopteris tenggerensis (Thelypteridaceae) are described as new species. Of these, only the last-named species is confined to Java, as at present known.